The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4097/kjae.2011.61.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the central venous pressure from internal jugular vein and the pressure measured from the peripherally inserted antecubital central catheter (PICCP) in liver transplantation recipients

Abstract: BackgroundUnlike its use during stable conditions, central venous pressure (CVP) monitoring from a peripherally inserted central venous catheter (PICC) has not often been used in surgeries with significant hemodynamic alterations. The aim of this study was to evaluate the feasibility of measuring PICC pressure (PICCP) as an alternative to measuring centrally inserted central catheter pressure (CICCP) in adult liver transplantation (LT) patients.MethodsWe measured PICCP and CICCP simultaneously during each main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This is in line with Yun's performance, in 2011, in South Korea, which was tried among liver transplantation candidates (6). In contrast to Black (9), who realized that the two factors of narrow lumen and long size made the CVP measures higher by PICC, we found similar measures to what Latham and colleagues reported, in 2012, in the SA (7).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with Yun's performance, in 2011, in South Korea, which was tried among liver transplantation candidates (6). In contrast to Black (9), who realized that the two factors of narrow lumen and long size made the CVP measures higher by PICC, we found similar measures to what Latham and colleagues reported, in 2012, in the SA (7).…”
Section: Discussionsupporting
confidence: 91%
“…The dependence of the bias we measured on the dynamic characteristics of the catheter used (i.e., resistance to bolus injection) is indirectly supported by the fact that in our study the CVP, which is a static pressure measured in no-flow conditions, was unaffected by the type of catheter used, as shown previously [1][2][3][4][5][6]8].…”
Section: Discussionsupporting
confidence: 83%
“…Several studies demonstrated that PICCs are equivalent to centrally inserted catheters (CICCs) for central venous pressure (CVP) measurement [1][2][3][4][5][6] but there is no evidence they can replace CICCs for cardiac output measurement using TPTD.…”
Section: Introductionmentioning
confidence: 99%
“…The PICC should be referenced at the phlebostatic axis. [87][88][89][90][91] A shallow slope following a fast flush suggests PICC occlusion. 88 The CVP obtained from PICCs that support high-pressure infusions such as infusions of radiographic contrast media is also accurate.…”
Section: Aacn Practice Alertmentioning
confidence: 99%